East Asia and Pacific Cities : Expanding Opportunities for the Urban Poor - Baker, Judy L.; Gadgil, Gauri U. (World Bank, Washington, DC, 2017)
Urbanization in East Asia and the Pacific has created enormous opportunity for many. Yet the rapid growth of cities can also create challenges as national and local governments try to keep up with the needs of their growing populations. Among these challenges is a lack of affordable housing, resulting in increasing slums, deficits in basic service provision, and widening inequality for urban dwellers.